Find 3 ∫ C y z cos x d x + ( z sin x + sin z + cos ( y 3 ) ) d y + y ( sin x + cos z + 1 ) d z where C is the curve parameterised by x = cos 3 t , y = sin 3 t , z = t for 0 ≤ t ≤ π .
(from a recent test on Vector Calculus)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
im really sorry for this comment, but could you explain your solution, I saw calc III a while ago and i dont understand the way you solve it. Thank you anyway
Log in to reply
I can try; feel free to let me know if you need further clarifications.
As a mathematician, I'm used to phrase this stuff in terms of "forms," but in introductory maths and physics it is usually expressed in terms of vector fields. In the problem at hand, we are looking at the vector field F ( x , y , x ) = ( y z cos x , z sin x + sin z + cos ( y 3 ) , y ( sin x + cos z + 1 ) ) .
Did you learn about "conservative" vector fields? These can be characterised in various equivalent ways; (a) The circulation is always 0, (b) the line integral is path-independent (depending only on the end points of the oriented curve), and (c) c u r l ( F ) = 0 (if the vector field is defined on all of R 3 , as it is in our case). If a vector field is conservative, it has a "potential" f ( x , y , z ) , that is , a scalar field such that g r a d ( f ) = ∇ f = F . In this case, if C is a curve from A to B , we have a fundamental theorem for finding line integrals, analogous to the single-variable case: ∫ C F ⋅ d s = f ( B ) − f ( A ) .
The vector field F in our example is not quite conservative (check the curl), but if we split off the simple field ( 0 , 0 , y ) and write F ( x , y , z ) = G ( x , y , z ) + ( 0 , 0 , y ) , then the field G ( x , y , x ) = ( y z cos x , z sin x + sin z + cos ( y 3 ) , y ( sin x + cos z ) ) turns out to be conservative. You can find a potential f for G by integrating each component function partially and "reconciling" the answers (as I call it in my classes). For example, for the first component you get f ( x , y , z ) = ∫ y z cos ( x ) d x = y z sin ( x ) + p ( y , z ) . If you proceed analogously for all three components, you end up with f ( x , y , z ) = y z sin x + y sin z + F ( y ) where F ′ ( y ) = cos ( y 3 ) (try it yourself and feel free to ask if you have more questions). Now you can apply the fundamental theorem, ∫ C G ⋅ d s = f ( B ) − f ( A ) = f ( − 1 , 0 , π ) − f ( 1 , 0 , 0 ) = 0 .
We can easily do the remaining line integral over the simple vector field ( 0 , 0 , y ) directly, by using the given parameterisation: ∫ C y d z = ∫ 0 π sin 3 t d t = 3 4 .
As you see in Mr Hennings solution, you can also do the whole problem simply by using the parameterisation and "plowing through it," but I suggest that you familiarise yourself with the special techniques we have for conservative vector fields.
I hope this makes some sense; please let me know.
Using the parametrization, this integral becomes 3 ∫ 0 π [ d t d ( t sin 3 t sin ( cos 3 t ) + sin 4 t ) + 3 cos ( sin 9 t ) sin 2 t cos t + sin 3 t ] d t The first term integrates to 3 [ t sin 3 t sin ( cos 3 t ) ] 0 π = 0 The second term integrates to 0 since the integrand is antisymmetric about t = 2 1 π (and so changes sign under the substitution t ↦ π − t ). Thus this line integral collapses to 3 ∫ 0 π sin 3 t d t = 4
Wow, this is impressive, you actually worked it out, with a nice use of symmetry. Quite a bit of computation is involved, though. Maybe we will get another solution showing an alternative (ultimately equivalent) approach, requiring less computation, or I will post it myself.
Problem Loading...
Note Loading...
Set Loading...
The given form can be written as ω = η + y d z , where η is exact with a potential of f ( x , y , z ) = y z sin x + y sin z + F ( y ) where F ′ ( y ) = cos ( y 3 ) . Considering the endpoints A ( 1 , 0 , 0 ) and B ( − 1 , 0 , π ) of the curve C , we have ∫ C η = f ( B ) − f ( A ) = 0 . We are left with 3 ∫ C y d z = 3 ∫ 0 π sin 3 t d t = 4 .